Upregulation of Phosphodiesterase 2A Augments T Cell Activation by Changing cGMP/cAMP Cross-Talk - Kurelic, Roberta; Krieg, Paula F.; Sonner, Jana K.; Bhaiyan, Gloria; Ramos, Gustavo C.; Frantz, Stefan; Friese, Manuel A.; Nikolaev, Viacheslav O. (Frontiers in Pharmacology, 2021)
3',5'-cyclic adenosine monophosphate (cAMP) is well-known for its diverse immunomodulatory properties, primarily inhibitory effects during T cell activation, proliferation, and production of pro-inflammatory cytokines. A decrease in cAMP levels, due to the hydrolyzing activity of phosphodiesterases (PDE), is favoring inflammatory responses. This can be prevented by selective PDE inhibitors, which makes PDEs important therapeutic targets for autoimmune disorders. In this study, we investigated the specific roles of PDE2A and PDE3B in the regulation of intracellular cAMP levels in different mouse T cell subsets. Unexpectedly, T cell receptor (TCR) activation led to a selective upregulation of PDE2A at the protein level in conventional T cells (Tcon), whereas no changes were detected in regulatory T cells (Treg). In contrast, protein expression of PDE3B was significantly higher in both non-activated and activated Tcon subsets as compared to Treg, with no changes upon TCR engagement. Live-cell imaging of T cells expressing a highly sensitive Förster resonance energy transfer (FRET)-based biosensor, Epac1-camps, has enabled cAMP measurements in real time and revealed stronger responses to the PDE2A inhibitors in activated vs non-activated Tcon. Importantly, stimulation of intracellular cGMP levels with natriuretic peptides led to an increase of cAMP in non-activated and a decrease of cAMP in activated Tcon, suggesting that TCR activation changes the PDE3B-dependent positive to PDE2A-dependent negative cGMP/cAMP cross-talk. Functionally, this switch induced higher expression of early activation markers CD25 and CD69. This constitutes a potentially interesting feed-forward mechanism during autoimmune and inflammatory responses that may be exploited therapeutically.